EFEK EKSTRAK BUAH JAMBLANG TERHADAP PERTUMBUHAN STREPTOCOCCUS MUTANS SEBAGAI PENYABAB UTAMA KARIES: EFFECT OF JAMBLANG'S FRUIT EXTRACT TI STREPTOCOCCUS MUTANS GROWTH AS MAIN AGENT OF CARIES - Santi Chismirina; Poppy Andriyani; Nopi Yanti Fitri (Dentika: Dental Journal, 2011)
Dental caries is a local infection disease and progressive on tooth. Streptococcus mutans (S. mutans). is one of causal factors of dental caries. Lactid acid that produced by S. mutans cause mineral on teeth become dissolve and this process is known as demineralization. Some studies done to find save material for dental caries therapy such as using natural things like jamblang fruit (Syzygium cumini). Jamblang’s fruit (Syzygium cumini) has a big potential using to prevent dental caries because the pharmacologic effect of it as antibacterial. The purpose of this study was to determine the effect of jamblang’s fruit extract to S. mutans growth. The method used in this study was by exposing S. mutans to 10-100% concentration of jamblang’s fruit extract. Then, colony of S. mutans was counted by using colony counter. The results of this study showed that jamblang’s fruit extract (Syzygium cumini) can reduce the growth of S. mutans colonies. The minimal concentration of it is 50% and the optimal concentration are 80%, 90%, and 100%. Atsiri oil, triterpenoid, phenol like flavonoid and tannin are suspected as main factors that caused inactivation of glucocyltransferase and fructocyltransferase of S. mutans. In conclusion, jamblang’s fruit (Syzygium cumini) has an ability to inhibit the growth of S. mutans colonies.